PRAKTIK ADAT BERCIYAY DALAM PERNIKAHAN MASYARAKAT TANJUNG HARAPAN KECAMATAN ELLA HILIR KABUPATEN MELAWI PERSPEKTIF URF - Syawaludin, Syawaludin; Haliah, Dahlia; Fadhil, Moh (Al-Usroh, 2025)
This research aims to examine: 1) The procession of traditional berciyay in weddings among the people of Tanjung Harapan, Ella Hilir District, Melawi Regency; 2) The ‘urf perspective on the customary practice of berciyay within marriage traditions in the same community. This study employs qualitative research methods through field research, utilizing historical, sociological, and normative approaches to comprehensively analyze the phenomenon. Data sources consist of primary and secondary sources: primary sources include traditional leaders, religious leaders, and community figures; secondary sources encompass books, journals, and relevant scholarly articles. Data collection techniques involve in-depth interviews, direct observation, and documentation. Data analysis is conducted through data reduction, data presentation, and drawing conclusions. Based on the analysis, the researchers concluded that: 1) the implementation of traditional berciyay involves several ritual stages, namely: dudok sentetai (sitting parallel), betepas (sweeping), drinking water blessed with prayers for safety and protection from misfortune, ketupat lepas, nimok aik (bailing water), dismantling the flower garden, and throwing a complete set of the couple’s clothes accompanied by a water fight; 2) the practice of berciyay among the people of Tanjung Harapan falls under the category of al-urf al-khas (specific custom) as it is confined to a particular regional community, and it is also classified as urf fasid (corrupt custom) due to several harmful aspects in its implementation, including the use of unclean water such as ditch water, fermented durian (tempoyak), or oil-contaminated water, unrestricted mixing between non-mahram men and women, physical contact during the water fight, and the potential for physical injuries or conflicts.